Karakteristik Hak Cipta Sebagai Objek Jaminan Fidusia - Merry Tjoanda (Batulis Civil Law Review, 2020)
A creator has the exclusive right to enjoy his own creation or to give permission to others to use his creation. The purpose of this study is to examine the characteristics of copyright that have the prospect of being used as collateral for credit, because copyright has economic value and can be transferred either entirely or partly because of inheritance, grants, wills, written agreements or other justified reasons. by laws and regulations. The method used is a type of normative legal research with a statutory approach and a conceptual approach. The results show that the characteristics of copyright as a fuduciary guarantee, which is an intangible movable object, can be used as an object of fiduciary security, even though the determination of the value or nominal value of copyright has no standard provisions, but parties can ask for advice from experts.